Class of Differential Equations of Combined Hadamard and Riemann-Liouville Operators - Bezziou, Mohamed; Dahmani, Zoubir; Slimane, Ibrahim (Sarajevo Journal of Mathematics, 2022)
This paper deals with the study of a class of nonlinear coupled equations of Riemann-Liouville fractional differential equations with Hadamard fractional integral nonlocal conditions. The existence of solutions is established by the Schauder fixed point theorem. Another result is proved using Leray-Schauder’s degree. Finally, some illustrative examples are discussed.